2018
DOI: 10.3390/min8070291
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry and Biomarker Analysis of the Bentonites from Esquivias (Toledo, Spain)

Abstract: The Tajo Basin is one of the richest in Mg-clays known around the world. Mg-bentonites, kwon as pink clays and green clays, alter in the Intermediate Unit of the Miocene sediments. In this work, a new approach to the genesis of these bentonites is performed by studying for the first time the biomarkers present in these clays in relation to the mineralogy and geochemistry, as well as using discriminatory criteria between green and pink clays. Samples were collected at a quarry of Mg-bentonites, in the proximiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In addition, as shown by the XRD patterns, the Green Clays had higher impurity contents (illite, quartz, and feldspar), while the Pink Clay samples usually were pure smectite, almost devoid of other minor minerals. This is related to the inherited character of the Green Clays versus the autigenic origin of the Pink Clays formed in the sedimentary basin, as indicated by Garcia-Rivas et al [77].…”
Section: Smectite Crystal Chemistrymentioning
confidence: 85%
See 1 more Smart Citation
“…In addition, as shown by the XRD patterns, the Green Clays had higher impurity contents (illite, quartz, and feldspar), while the Pink Clay samples usually were pure smectite, almost devoid of other minor minerals. This is related to the inherited character of the Green Clays versus the autigenic origin of the Pink Clays formed in the sedimentary basin, as indicated by Garcia-Rivas et al [77].…”
Section: Smectite Crystal Chemistrymentioning
confidence: 85%
“…On the other hand, the Pink Clays are pure smectites of stevensitic composition without detrital minerals that correspond to levels of authigenic clays newly formed in the sedimentary basin, which appear interbedded in the Green Clay unit [71]. García-Rivas et al [77] (from the geochemistry and biomarker criteria) have concluded that the Green Clays have a more detrital character than the Pink Clays do, which present a more authigenic character. De Santiago et al [78] (from TEM observations) have concluded that Pink smectites have a cellular texture that resembles descriptions of primitive clay precursors that were formed from glasses, gels, or the weathering of previous minerals.…”
Section: The Tajo Basinmentioning
confidence: 99%
“…All trioctahedral samples were collected at the Tajo Basin (Spain) and they belong to the same unit, the Pink Clays Unit, so their chemical compositions should be similar. These clays have been studied by different authors and have been characterized as stevensite (Cuevas et al, 1993(Cuevas et al, , 2003de Santiago Buey et al, 2000;García-Rivas et al, 2018), kerolite or interstratified kerolite/stevensite (Martin de Vidales et al, 1991;Pozo et al, 1992Clauer et al, 2012), and as a fine-grained interstratification of turbostratic talc and saponite (Steudel et al, 2017). The lack of agreement on the classification of Pink Clays is easily understood by considering the chemical compositions and structural formulae obtained from our natural samples.…”
Section: Simentioning
confidence: 87%
“…Three samples (ESB6, RESQ and ROS) were collected at the Tajo Basin, located in the centre of the Iberian Peninsula. They are sedimentary clays belonging to the Pink Clays Unit (Martin de Vidales et al, 1991;Pozo et al, 1992;Cuevas et al, 1993;de Santiago Buey et al, 2000;Cuevas et al, 2003;García-Rivas et al, 2018;García-Romero et al, 2019). Tajo Basin is particularly interesting because it is one of the richest basins for Mg clays in the world, with high economic value.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation